2019
DOI: 10.1038/s41380-019-0519-9
|View full text |Cite
|
Sign up to set email alerts
|

Pianp deficiency links GABAB receptor signaling and hippocampal and cerebellar neuronal cell composition to autism-like behavior

Abstract: Pianp (also known as Leda-1) is a type I transmembrane protein with preferential expression in the mammalian CNS. Its processing is characterized by proteolytic cleavage by a range of proteases including Adam10, Adam17, MMPs, and the γ-secretase complex. Pianp can interact with Pilrα and the GB1a subunit of the GABAB receptor (GBR) complex. A recent case description of a boy with global developmental delay and homozygous nonsense variant in PIANP supports the hypothesis that PIANP is involved in the control of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
(104 reference statements)
1
7
0
Order By: Relevance
“…For female presentations, 71% (n = 5) included ambiguous genitalia and 2 patients (29%) presented with clitoromegaly, one of 2). We first published PIANP, which encodes a protein that regulates glutamate release in the brain, in the context of intellectual disability (Anazi et al, 2017;Winkler et al, 2019). This previously reported patient (15DG0989) with global developmental delay (GDD) presented with bilateral undescended testes, hypotonia, almond-shaped eyes, tapered fingers, and prominent forehead (Figure 1).…”
Section: Demographicsmentioning
confidence: 99%
“…For female presentations, 71% (n = 5) included ambiguous genitalia and 2 patients (29%) presented with clitoromegaly, one of 2). We first published PIANP, which encodes a protein that regulates glutamate release in the brain, in the context of intellectual disability (Anazi et al, 2017;Winkler et al, 2019). This previously reported patient (15DG0989) with global developmental delay (GDD) presented with bilateral undescended testes, hypotonia, almond-shaped eyes, tapered fingers, and prominent forehead (Figure 1).…”
Section: Demographicsmentioning
confidence: 99%
“…The involvement of the cerebellum in higher processes of cognition and emotion [1,2] and its relevance as a locus for a range of disorders and diseases make this simple yet elusive structure an important model in a number of fields. Cellular and anatomical dysfunction of the cerebellum has been associated with psychological disorders, such as autism, attention deficit, hyperactivity or schizophrenia [3][4][5][6][7][8]. In recent years, our understanding of some of the more familiar aspects of cerebellar growth, such as its territorial allocation and the origin of its various cell types, has undergone major recalibration.…”
Section: Introductionmentioning
confidence: 99%
“…EMT, an essential regulatory process that mediates invasion and metastasis, is considered a culprit of metastasis in CRC 29 . There are many pathways upstream of EMT, such as Wnt/β-catenin, JNK, and TGF-β 25 , 26 . In this study, the expression of EMT-related molecules N-cadherin and Vimentin were found to be elevated, and E-cadherin was suppressed (at the protein and mRNA level) in GABABR1 knockdown RKO and Lovo cells.…”
Section: Discussionmentioning
confidence: 99%
“…As an inhibiting neurotransmitter, previous prospective studies on GABABR mainly involved neurons, neuropathic pain and neuroinflammation [23][24][25]. The role of GABABR in cancer has received increasing attention in recent years.…”
Section: Discussionmentioning
confidence: 99%